2015
DOI: 10.1007/s00586-015-4235-0
|View full text |Cite
|
Sign up to set email alerts
|

A new 3-dimensional method for measuring precision in surgical navigation and methods to optimize navigation accuracy

Abstract: This new technique evaluating precision of screw placement in 3 dimensions improves the ability to define screw placement. Pedicle screw position at final imaging showed the use of StealthStation navigation to be accurate and safe. As this is a preliminary evaluation, we have identified several factors affecting the precision of pedicle screw final position relative to that predicted with navigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 48 publications
2
22
1
1
Order By: Relevance
“…In our study, we saw a malposition and need for correction in only 1.9% of pedicle approaches (3/154). 98.1% of accurate pedicle approaches is an excellent result of our series compared to the previous studies with rates ranging from 78 to 100% in open and MIS surgical procedures [14,[24][25][26][27][29][30][31]. The fact that an additional haptic control of intrapedicular course of the implant is not possible in MIS surgery did not have any effect on accuracy in our series.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our study, we saw a malposition and need for correction in only 1.9% of pedicle approaches (3/154). 98.1% of accurate pedicle approaches is an excellent result of our series compared to the previous studies with rates ranging from 78 to 100% in open and MIS surgical procedures [14,[24][25][26][27][29][30][31]. The fact that an additional haptic control of intrapedicular course of the implant is not possible in MIS surgery did not have any effect on accuracy in our series.…”
Section: Discussionsupporting
confidence: 55%
“…Miekisiak et al found an accuracy of 79% in free-hand administered pedicle screws in a series leading to 2 revisions in 85 cases [28]. Kleck et al published an accuracy of 94% in a CT-based navigation series using the O-arm CTguided navigation technique distributed by Medtronic [29]. Kraus et al saw an accuracy of 90.3% (< 2 mm breaching) in fluoroscopy navigation-guided pedicle screws compared to 94.6% in the standard technique pedicle screws in the thoracic and lumbar spine.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the inserted screws relative to the planned path was measured on postoperative 3D scans to assess technical accuracy. 8 , 9 The angular deviation was measured in the axial as well as in the sagittal plane. 9 11 Figure 3 depicts the technical accuracy and angular deviation measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of this study is higher than the accuracy of other studies, and the stability of the system is excellent. As early as 2016, Kleck et al [37] employed the O-arm and StealthStation to evaluate the accuracy of the three-dimensional navigation of the pedicle screw. The obtained navigation accuracy is approximately 5.9 ± 3.5 mm.…”
Section: Comparison Of Spine Surgery Without Robotic Assistance Basedmentioning
confidence: 99%